Interpreting Abraham: journeys to Moriah - Beach, Bradley (Fortress Press, 2014)
Judaism: Jewish uses of the Akedah: Genesis 22:1-19 John H. Spitzer -- Christianity: traditional Christian interpretation of Genesis 22 Carey Walsh -- Islam: engaging with Abraham and his knife: interpretation of Abraham's sacrifice in the Muslim tradition Isra Yazicioglu -- Kant: the attack on Abraham Ronald Green -- Hegel: abductive inference, autonomy, and the faith of Abraham Preston Stovall -- Kierkegaard: resignation and the "humble courage of faith" in Kierkegaard's Fear and trembling Andrew Tebbutt -- Kafka: a tale of two Abrahams Matthew T. Powell -- Levinas: unbinding the other: Levinas, the Akedah, and going beyond the subject Laurence Bove -- Derrida: Derrida and the test of secrecy Chris Danta -- Our journeys to Moriah Bradley Beach